Fiscal Decentralization of East Lampung Regency 2020 – 2024 Study of Local Government Financial Performance Index and Ratio Analysis - Miftahul Arifin; Feni Rosalia (SOSIOEDUKASI, 2025)
This research aims to examine how fiscal decentralization can be effective in East Lampung Regency during the 2020-2024 fiscal years using the indicator and regional financial ratio approach method. This research examines regional fiscal autonomy, government transfer efficiency, and the management of Regional Original Revenue (PAD). The research is a quantitative descriptive study where secondary data will be obtained as represented by the East Lampung Regency Regional Revenue and Expenditure Budget (APBD) Realization Report for the relevant period. The research results show that the average fiscal independence index (IKF) is only 8.13%, which indicates significant dependence on central transfer funds. Similarly, the Fiscal Decentralization Level (DDF) is only 8.2, indicating that the region has low fiscal capacity. Comparing regional revenue performance shows that it significantly decreased in 2024 compared to 2020 (from 102.93% to 36.04%). Although the quality of government transfers is relatively high (97% to 99%), these funds are not sufficient to compensate for the deteriorating local revenue sources. Additionally, there was an overall average decline in capital expenditure of -14.2% per year, indicating that fiscal policy is still characterized by normal business spending rather than development-oriented investment. In conclusion, fiscal decentralization in East Lampung Regency has not yet met the desired goals within the broader scope of regional autonomy. Local fiscal performance still relies on central transfer funds, and the potential for local revenue has not been fully utilized. This paper suggests reforms in local revenue management, strengthening fiscal institutional capacity, and performance-based budgeting to enhance local fiscal autonomy.